Numerical solution of MHD flow of power law fluid subject to convective boundary conditions and entropy generation - Waleed Ahmad Khan, M.; Ijaz Khan, M.; Hayat, T.; Alsaedi, A. (Computer methods and programs in biomedicine, 2020)
•An explicit solution for two dimensional flow of power law fluid is discussed.•Convective boundary conditions on temperature are implemented.•Viscous dissipation has been taken into account.•Concentration equation has been assisted with simple chemical reaction. The application of entropy optimization has consistently incorporated in traditional and industrial fields. The system is permanently sustainable, usually a final ideal structure may not exist in general, as common evolution shows trends in a long time. The measurement of the entropy generation related to heat transport can be proportional to temperature difference. The minimization of entropy generation through various parameters is our main purpose in this research article. Therefore, here we have discussed 2D flow of non-Newtonian liquid over a stretched surface with entropy optimization. Convective boundary conditions of temperature are implemented in the current flow phenomenon. Furthermore, viscous dissipation has been taken into account. The involved nonlinear differential system has been tackled through ND solve numerical technique (Shooting method). The key observations are summarized as follows: (i) Velocity grows for larger estimations of power law index of fluid. (ii) Temperature θ˜(ξ) increases for Ec. (iii) Surface drag enhances for higher values of Ha. (iv) The temperature gradient NuxRe−1n+1 is inversely proportional to Ec and Ha. (v) Entropy NG(ξ) is larger for higher Ec and Ha while the opposite impact is examined for M. (vi) Bejan number Be decreases with Prand M, while it upsurges with Ha and Ec.